2015
DOI: 10.1118/1.4921362
|View full text |Cite
|
Sign up to set email alerts
|

Dosimetric characterization and organ dose assessment in digital breast tomosynthesis: Measurements and Monte Carlo simulations using voxel phantoms

Abstract: Taking into account an average breast with a thickness of 4.5 cm, the MGDs for DM and DBT acquisitions were below the achievable value (2.0 mGy) defined by the European protocol. Additionally, in the case of a fusion imaging study (DM + DBT), the MGD for a 4.5 cm thick breast is of the order of 1.88 ± 0.36 mGy. Finally, organ dose evaluations underline the need to improve awareness concerning dose estimation of DBT exams for some organs, especially when radiation risk is assessed by using the effective dose.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
30
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(32 citation statements)
references
References 50 publications
(63 reference statements)
2
30
0
Order By: Relevance
“…The caveat associated with acquiring both sets of images is that the patient sees a twofold increase in the dose, since acquisition of a single DBT view can impart a mean glandular dose of up to 2.28 mGy. 161 However, one study which assessed radiologist reporting of 2D mammograms synthesized from DBT data compared with digital mammograms acquired by conventional means found that the use of either mammogram resulted in similar rates of truepositive and FP reporting. 162 The comparable magnitudes of detection sensitivity and FP reporting among digital mammograms and DBT-synthesized mammograms thus show promise for the employment of DBT-synthesized mammograms as an alternative to the acquisition of a conventional digital mammogram.…”
Section: Breast Screeningmentioning
confidence: 99%
“…The caveat associated with acquiring both sets of images is that the patient sees a twofold increase in the dose, since acquisition of a single DBT view can impart a mean glandular dose of up to 2.28 mGy. 161 However, one study which assessed radiologist reporting of 2D mammograms synthesized from DBT data compared with digital mammograms acquired by conventional means found that the use of either mammogram resulted in similar rates of truepositive and FP reporting. 162 The comparable magnitudes of detection sensitivity and FP reporting among digital mammograms and DBT-synthesized mammograms thus show promise for the employment of DBT-synthesized mammograms as an alternative to the acquisition of a conventional digital mammogram.…”
Section: Breast Screeningmentioning
confidence: 99%
“…This is in agreement with the phantom study reported by Ali et al (9.5 μGy measured by thermoluminescence dosimeter in an ATOM phantom) [ 22 ]. Baptista et al [ 10 ], using MCS, found a thyroid dose of 0.273 mGy for the CC view with a corresponding breast MGD of 2 mGy. Compared to our MCS and those reported in the literature, this result is surprisingly high for the organ dose value.…”
Section: Discussionmentioning
confidence: 99%
“…In the study by Whelan et al [ 7 ], the radiation dose to the skin overlying the thyroid for 91 women undergoing routine screening mammography was measured while the study by Chetlen et al [ 8 ] included 207 women. Baptista et al [ 10 ] compared exposition of organs caused by digital mammography and digital breast tomosynthesis by measurements and Monte Carlo simulation (MCS). For a bilateral digital mammography in craniocaudal (CC) view, a thyroid dose of 0.273 mGy was found by these authors.…”
Section: Introductionmentioning
confidence: 99%
“…MGD from DBT is currently reported to be one to two times more than that from single view FFDM. 15 Feng and Sechopoulos 4 estimated the MGD resulted from single craniocaudal view acquired by FFDM and DBT. They concluded that DBT resulted in higher MGD than FFDM and this difference increases as the breast thickness increase.…”
Section: Introductionmentioning
confidence: 99%
“…Other organs radiation dose, excluding exposed breast tissue, from DBT was assessed by Baptista et al 15 They used Monte Carlo simulation software to estimate the radiation dose received by several radiosensitive organs within the female reference voxel Laura phantom from DBT exposure. In order to simulate different breast thickness, the organ radiation doses were estimated using different tube potentials, 24-34 kVp, and 100 mAs.…”
Section: Introductionmentioning
confidence: 99%